Experimental and theoretical analysis of hydraulic fracturing and gas fracturing of rock under true triaxial compressions. (July 2020) - Lu, Yinlong; He, Mengqi; Wu, Bingzhen; Meng, Xingyu
Highlights: A test system is developed for true triaxial hydraulic and gas fracturing. Longitudinal or transverse fracture appears under true triaxial compression. Analytical solutions for fracture initiation and breakdown pressures are proposed. Theoretical predictions agree well with the test observations. A dynamic pulsed gas fracturing method is proposed and tested. Abstract: A test system was developed for true triaxial hydraulic fracturing (HF) and gas fracturing (GF) combined with acoustic emission (AE) monitoring and 3D computerized tomography (CT) scanning reconstruction to carry out a series of HF and GF tests under different true triaxial loading conditions. The critical breakdown pressure characteristics, the AE activities, and the fracture propagation and spatial morphologies were obtained during the fracturing process. The test results showed that the GF breakdown pressure was approximately 29.0–31.3% less than the HF breakdown pressure. Moreover, for the GF specimen, the gas pore pressure induced a large number of new microfractures before critical fracture. However, both HF and GF under true axial compression can only produce simple main longitudinal fractures (LFs, along the borehole) and transverse fractures (TFs, across the borehole) that are strictly dependent on the initial true triaxial stress field. Based on the experimental observations, a hypothesis for the initiation of the HF and GF under true triaxial compression was proposed by using the maximum tangential stress on the borehole wall and the maximum axial stress along the borehole. Accordingly, analytical solutions of the critical breakdown pressure for the HF (impermeable) and GF (permeable) specimens were derived. The theoretical predictions agree well with the observations from the 3D numerical simulations and tests. Lastly, a novel pulsed GF method (dynamic loading fracturing) was proposed to overcome the dependence of the in-situ crustal stress field associated with traditional HF and GF methods (static loading fracturing). Laboratory test results showed that the dynamic pulsed GF at moderate pressure can generate a complex and random fracture network independent of the in-situ stress field in rock.